PROBLEMS OF RESTRUCTURING THE ECONOMY OF THE REGION OF THE AGRARIAN-INDUSTRIAL TYPE - I. Kuznetsov; A. Sayapin; O. Polushkina (Вестник Северо-Кавказского федерального университета, 2022)
This article presents the results of the study of structural processes in the economy of the Tambov region as an agrarian-industrial region, the periphery of the economy of which is manifested, among other things, in the features of the restructuring of traditional enterprises and industries over the past twenty years. The purpose of this study is to develop the hypothesis that restructuring as a microeconomic process is not carried out independently, but in accordance with structural changes in higher-level systems (regional economic systems), therefore, in the analysis of restructuring processes, it is necessary, along with the institutional and macro-economic components, to introduce a structural component. The article also presents a retrospective of the restructuring of the regional economy and presents a vision of the optioorganizational development of the regional economy in the current conditions.